CLINICAL AND ETIOLOGICAL PROFILE OF PATIENTS PRESENTING WITH ASCITES IN A TERTIARY CARE HOSPITAL - DALABEHERA, SOUMYA; Mohanty, Sriprasad; Behera, Bijaya Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Ascites is one of the common clinical problems confronting a physician, with a myriad of causes behind. Early detection and evaluation of the causes of ascites help in effective management and lessens complications. However, there is lack of data regarding the prevalence of causes of ascites in our set-up. Hence, this study was conducted in our tertiary care hospital to study the clinical profiles and etiological factors of patients with ascites. Methods: This prospective and observational study was carried out in the Department of General Medicine of S.C.B. Medical College and hospital, Cuttack, Odisha, India, from September 2019 to November 2021. Hundred patients of ascites of either sex >18 years of age admitted in the medicine ward fulfilling the inclusion and exclusion criteria were included in this study and were thoroughly evaluated after obtaining informed consent. All the patients were subjected to detailed history taking, thorough physical examination and routine laboratory evaluation such as complete blood count, random blood sugar, liver function test, renal function test, serum protein and albumin, serum electrolytes, prothrombin time, international standardized ratio, hepatitis B surface antigen, and antibody to hepatitis C. Hepatic encephalopathy, when present, was classified into four grades according to West Haven criteria. Ultrasonography of abdomen and pelvis, Digital chest X-ray PA view, and ECG were done in all the patients. Results: In the present study of 100 patients, major cause of ascites was found to be cirrhosis of liver (64%) followed by tuberculosis (10%), malignancy (9%), heart disease (7%), and nephrotic syndrome (3%). The major cause of the cirrhosis of liver was alcoholism (64%) followed by hepatitis B (15.6%), Non-alcoholic steatohepatitis (14.1%), Hepatitis C (4.7%), and cryptogenic (3.1%). Complications such as hepatic encephalopathy and spontaneous bacterial peritonitis were observed in 17% and 7.8% cases of ascites, respectively. Conclusion: Cirrhosis of liver was found to be the most common cause of ascites in our study followed by tuberculosis and malignancy. Alcoholism was the most common cause of cirrhosis followed by chronic hepatitis B.